Perspektif Hadis Tentang Teori Belajar Behavioristik (Studi Kitab Ar-Rasul Al-Muallim) - Zaimul Ihsan; Wahidah Fitriani (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2022)
This study examines hadiths that are directly related to behavioristic learning theory in concept and practice. The formulation of learning theories by western experts does not necessarily deny the concepts and teachings of the Prophet who have already perfected theory and practice. This research uses literature study techniques to obtain qualitative results by being described using data reduction methods from various sources, then displayed properly. The result of this study is that the application of this behavioristic learning theory has been preceded by the Messenger of Allah as the best educator of all time. The important concept of the environment as a shaper of behavior (charity) has been explained in the noble hadith. Regarding stimulus (motivation / reward or punishment) and response has also been practiced by him Saw. Likewise, the important role of learning preparation, practice and repetition as well as impact analysis, as well as rewarding and response to dislike behavior then gently reprimanding is a concept that has been used by the Prophet since long ago.